Animal Husbandry and Nutrition 2018
DOI: 10.5772/intechopen.76972
|View full text |Cite
|
Sign up to set email alerts
|

Managing Dietary Energy Intake by Broiler Chickens to Reduce Production Costs and Improve Product Quality

Abstract: Feeding constitutes the highest variable cost in poultry production, accounting for at least 60% of such costs, especially in an intensive rearing system. Energy intake is an essential factor in broiler production because of its involvement in growth rate, carcass quality as well as its role in the development of certain metabolic diseases. Dietary energy is supplied in broiler nutrition through different feed resources. Dietary energy content strongly regulates feed consumption, and energy is the most expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 87 publications
(99 reference statements)
0
28
0
3
Order By: Relevance
“…En cuanto al CA, este fue ligeramente superior en los animales alimentados ad libitum, registrándose un valor promedio total de 4181.01 ± 306.46 g entre tratamientos, muy similar al calculado por Henn et al (37); Mendes et al (44), e InfanteRodríguez et al (45). Sahraei (12) afirma que la tasa de crecimiento está relacionada con el CA, por lo que la restricción alimenticia podría inhibir considerablemente la GTP; sin embargo, el análisis estadístico arrojó que el CA registrado en el T 3 y T 4 , fue significativamente menor (p < 0.05) con respecto al grupo control, en tal sentido, los criterios prácticos de análisis productivo empleados actualmente por los avicultores, sugieren que el valor calculado de CA en el T 4, probablemente ejerce un impacto económico significativo, considerando que la alimentación constituye el costo variable más alto (46). En la Figura 1-B se ilustra el comportamiento de la variable CA durante la experiencia en campo, y se observa que, a pesar de la disminución del consumo durante la restricción, al final del ensayo todos los grupos alcanzaron valores de ingesta similares al tratamiento control, tal y como fue reseñado por Hassanabadi y Moghaddam (47).…”
Section: Análisis Estadísticounclassified
“…En cuanto al CA, este fue ligeramente superior en los animales alimentados ad libitum, registrándose un valor promedio total de 4181.01 ± 306.46 g entre tratamientos, muy similar al calculado por Henn et al (37); Mendes et al (44), e InfanteRodríguez et al (45). Sahraei (12) afirma que la tasa de crecimiento está relacionada con el CA, por lo que la restricción alimenticia podría inhibir considerablemente la GTP; sin embargo, el análisis estadístico arrojó que el CA registrado en el T 3 y T 4 , fue significativamente menor (p < 0.05) con respecto al grupo control, en tal sentido, los criterios prácticos de análisis productivo empleados actualmente por los avicultores, sugieren que el valor calculado de CA en el T 4, probablemente ejerce un impacto económico significativo, considerando que la alimentación constituye el costo variable más alto (46). En la Figura 1-B se ilustra el comportamiento de la variable CA durante la experiencia en campo, y se observa que, a pesar de la disminución del consumo durante la restricción, al final del ensayo todos los grupos alcanzaron valores de ingesta similares al tratamiento control, tal y como fue reseñado por Hassanabadi y Moghaddam (47).…”
Section: Análisis Estadísticounclassified
“…The vegetable oils from various sources are added to different feedstuff of poultry birds to meet their energy deficiencies. In this regard soybean oil, sunflower and canola oil are among some of the important vegetable oils used in poultry production to coup up the energy deficiencies (Ahiwe et al 2018). In this context, a number of research trials have been conducted on the use of oils from different sources in poultry (Jalali et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils and animal fats are usually added to animal diets to increase dietary energy concentration (Ravindran et al, 2016). Since oils and fats confer at least twice as much energy as other food nutrients such as carbohydrates and proteins (Ahiwe et al, 2018;Blair, 2018), there is a greater demand in optimizing the use of these products to meet the energy requirements of poultries (Ravindran et al, 2016). Furthermore, high fat feeding in poultry has been proven to improve the digestibility and absorption of non-lipid constituents (Blair, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the fat utilization in broilers was age dependent where fat utilization improved with age . Animal nutritionists often struggle to formulate feed with adequate energy intake due to the variation of the nutritional values in oil and fat samples that can lead to reduction in the performances of the DOI: https://dx.doi.org/10.51227/ojafr.2020.21 animals and substantial economic losses (Niu et al, 2009;Ahiwe et al, 2018). A better understanding of the AME of different oil and fat samples can be gained by incorporating the FFA and U:S data into the Wiseman equation to generate information on the quality of the oil and fat samples; this will allow nutritionists to make informed decisions on their use for feed formulation to achieve consistent animal performance.…”
Section: Introductionmentioning
confidence: 99%